Public perceptions of cultural ecosystem services provided by beach nourishment and eelgrass restoration in southern Sweden. Issue 1 (2nd November 2022) - Van Well, Lisa; Isayeva, Anelya; Axel Olsson, Pål; Hollander, Johan
Abstract : Ecosystem‐based protection is becoming a viable adaptation option to conventional engineered solutions to rising sea levels and coastal erosion. While the environmental and biological ecosystem services provided by ecosystem‐based adaptation measures such as beach nourishment and/or seagrass plantations are being acknowledged and analysed, less attention has been paid to the social or cultural dimensions of these services. This paper builds upon the emerging body of research that explores cultural ecosystem services in coastal areas and how they are perceived by the people who live, work and recreate in these areas. The aim of the paper is to take stock of and understand public and stakeholder perceptions of the cultural ecosystem services that may accrue through eelgrass Zostera marina restoration in tandem with beach nourishment in southern Sweden. The empirical research is based on an on‐line open‐ended questionnaire in the coastal municipalities of Båstad, Trelleborg, Ystad and Kristianstad. The results demonstrate that virtually all respondents had noticed a change in the coastline in recent years, mainly that the coastline had retreated. While beach nourishment measures were recognized among respondents to counter the shoreline erosion, there was very little understanding of the role that eelgrass plantations can play in creating biodiversity and benefits for society. Still, most acknowledged the importance of making room for water and biodiversity at the coast stating how the coastline was valued for primarily health and spiritual reasons. This knowledge will help local, regional and national decision‐makers and regulatory authorities to make evidence‐based choices for coastal protection, by complementing the analysis of environmental and physical ecosystem‐services with cultural and socio‐economic considerations. Nature‐based solutions such as eelgrass reintroduction or beach nourishment should be tailored to the values, perspectives and perceptions of the local communities to help ensure their continued contribution to biodiversity.